Історія, культура та освіта: християнський вимір. Вип. 7 - Хмельницький інститут ПрАТ «ВНЗ «МАУП» (My University, 2017)
У збірнику наукових праць вміщено статті ХІ Всеукраїнської науково-практичної конференції «Історія, культура та освіта: християнський вимір». Авторами статей розкрито такі питання: освіта в Україні: проблеми та перспективи; вищі навчальні заклади в ході реформування освітньої галузі; державотворчі процеси в юридичній та економічній сферах: сучасне осмислення; першоджерела в дослідженні історії України; просвітителі та сповідники Подільської землі; патріотизм і національна самобутність: духовні витоки; педагогіка духовності. The collection of scientific works contains articles of the XI All-Ukrainian Scientific and Practical Conference “History, Culture and Education: Christian Dimension”. The authors of the articles have revealed the following issues: education in Ukraine: problems and prospects; higher educational institutions in the course of reforming the educational sector; state-building processes in the legal and economic spheres: modern understanding; primary sources in the study of the history of Ukraine; educators and confessors of the Podolsk land; patriotism and national identity: spiritual origins; pedagogy of spirituality.